Pengelolaan Kampung Pecinan Sudiroprajan sebagai Daya Tarik Wisata Budaya di Surakarta - Pradipta, Made Prasta Yostitia; Satiti, Emmelia Nadira (Jurnal Pariwisata Terapan, 2024)
Sudiroprajan Chinatown has tourist attractions that can support cultural tourism attractions in Surakarta City. With multi-ethnic acculturation in terms of annual celebrations to the special foods available in Sudiroprajan Chinatown Village. However, due to the pandemic the Sudiroprajan Pokdarwis was no longer active and resulted in the paralysis of the tourist attraction icon in Sudiroprajan Chinatown Village. The purpose of this study is to find out what attractions exist in Sudiroprajan Chinatown Village and then to analyze the inhibiting factors for the development of tourist attractions and come up with some suggestions so that they can attract tourists to visit. To get the data in this research is to do direct observation, documentation, and direct interview with the Head of Pokdarwis Sudiroprajan and look for literature studies related to the research problem. The results obtained are many tourist attractions in the form of the Kali Pepe and Grebeg Sudiro river crossings. See the Lion Dance and various culinary delights. The obstacles found were regarding inconsistent management due to the large number of youth volunteers who have their own busy lives and finally the Covid-19 virus. Further research is suggested to expand the attraction of cultural tourism around the Surakarta City area.